2019
DOI: 10.1016/j.arabjc.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Ion exchange recovery of chromium (VI) and manganese (II) from aqueous solutions

Abstract: Sorption recovery of toxic ions -chromium (VI) and manganese (II) -from aqueous solutions with different acidity (0.001-0.5 M HCl) was investigated on cation and anion exchangers synthesized with long-chained cross-linking agents (LCA). The initial concentrations of Cr(VI) and Mn(II) were 1 g/L and 5 g/L, respectively. It was shown that the resins with LCA possess high ionic permeability due to the elasticity of polymeric skeleton. High selectivity and good kinetic properties of these sorbents allowed to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Ingesting large quantity of Cr(VI), either by human or animal, can be corrosive to the skin and eyes and causes stomach upsets and ulcers, convulsions, kidney and liver damage [72,73]. Allergic reactions consisting of severe redness and swelling of the skin have been noted.…”
Section: Cr(vi) Effects On Human Health and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingesting large quantity of Cr(VI), either by human or animal, can be corrosive to the skin and eyes and causes stomach upsets and ulcers, convulsions, kidney and liver damage [72,73]. Allergic reactions consisting of severe redness and swelling of the skin have been noted.…”
Section: Cr(vi) Effects On Human Health and Environmentmentioning
confidence: 99%
“…Krishnani et al [95] reported that the maximum permissible limits of Cr(VI) to discharge into potable water, in land surface water, and industrial wastewater are 0.05, 0.1, and 0.25 mg/L, respectively. According to the Moroccan official bulletin (NM 03.7.001), the Russian federation [73], and the Indian standard [65,94], the maximum allowable limits for Cr in drinking and domestic water are 0.05 and 0.5 mg/L for Cr(VI) and Cr(III), respectively.…”
Section: Standards and Regulations For Cr(vi)mentioning
confidence: 99%
“…Therefore, the development of an effective method to remove Cr(VI) from industrial wastewater is essential for water treatment. Various methods such as adsorption, reverse osmosis, ion exchange,, and electrocoagulation have been reported for the removal of Cr(VI) from water. However, these methods are sometimes expensive and often inefficient at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, different techniques have been employed such as ion exchange, [12,18] membrane separation, [31] reductive deposition method, [7] adsorption, [8,20] and electrocoagulation process. [2,17] Recent years, adsorption method has drawn much attention for its easy operation, wide availability, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%